(untitled) (Acta Entomológica Chilena, 2022)
The species Dichroplus elongatus is a phytophagous grasshopper following Gangwere’s classificalion it is an herbivorous species, because of the structure of the jaws, the observations made and the applied tests. Its diet consists of leaves of Gramineae and many others varied species of Dicotyledoneae. The species also consummes new stems and flowers of vegetable crops. The species is indeed polyphagous since eats a large variety of different vegetables of high valué of preference. This indícales a high density of populalion in very restricted areas. Due to this it is possible to find specimens during all summers and part of early fall. The natural vegetalion changes quickly in these areas because of the hot dry weather. As human intervention destroyes this habitat, the grasshoper then moves into new non affected habita ts.